2012
DOI: 10.1074/jbc.m112.408963
|View full text |Cite
|
Sign up to set email alerts
|

Clock Genes Influence Gene Expression in Growth Plate and Endochondral Ossification in Mice

Abstract: Background: Clock genes are expressed in different peripheral organs. Results: Rhythmic expression was lost with Ihh in the growth plate from mice defective of BMAL1 with a small body size. Conclusion: Endochondral ossification is under the control by clock genes in chondrocytes. Significance: Peripheral clocks are a target for treating cartilaginous diseases relevant to abnormal postnatal chondrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 36 publications
8
110
3
Order By: Relevance
“…PER and CRY proteins accumulate and multimerize in the cytoplasm during the day, then move back to the nucleus in the evening to inhibit CLOCK and BMAL1 activity, thus inhibiting their own transcription. Previous work identified autonomous cartilage circadian rhythms in mice that became dysregulated with age and upon chronic inflammation (11)(12)(13)(14). Moreover, environmental disruption of circadian rhythms in mice (mimicking chronic jet lag) predisposes knee cartilage to OA-like damage (15), further supporting the idea of an involvement of circadian rhythm disruption in OA development.…”
Section: Introductionmentioning
confidence: 56%
“…PER and CRY proteins accumulate and multimerize in the cytoplasm during the day, then move back to the nucleus in the evening to inhibit CLOCK and BMAL1 activity, thus inhibiting their own transcription. Previous work identified autonomous cartilage circadian rhythms in mice that became dysregulated with age and upon chronic inflammation (11)(12)(13)(14). Moreover, environmental disruption of circadian rhythms in mice (mimicking chronic jet lag) predisposes knee cartilage to OA-like damage (15), further supporting the idea of an involvement of circadian rhythm disruption in OA development.…”
Section: Introductionmentioning
confidence: 56%
“…It was previously demonstrated by Takarada et al that global deletion of BMAL1 results in decreased body size and weight and defective chondrogenesis, locomotor ability, and metabolism (11). The same group had also crossed BMAL1-floxed mice with a chondrocyte-specific Col2a1-Cre deleter strain (12) and showed that chondrocyte-specific deletion of BMAL1 results in bone development defects similar to those seen in global KO mice (11). The Dudek et al study (9) complements the previous study by addressing the role of BMAL1 in cartilage homeostasis in adult tissues.…”
Section: Wrist Watches: Cartilage Clocks In Articular Jointsmentioning
confidence: 99%
“…Researchers found that mice lacking the core clock genes, Bmal1 (Bmal1 -/ -), Clock (Clock -/ -), or Per2 (Per2 -/ -), showed early aging symptoms compared with their wild-type littermates [7][8][9], especially the Bmal1 -/ -mice, in which early aging symptoms were more obvious [10]. Studies also found that endochondral ossification was under control by clock genes in chondrocytes [11].…”
Section: Introductionmentioning
confidence: 99%